Manfaat Aktivitas Untuk Lanjut Usia Masa Pandemi Covid 19 Di Kelurahan Angke - Yohana; Eveline Margo; Juni Chudri; Meiyanti Meiyanti (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Elderly is a natural life cycle and cannot be avoided by every human being. Increasing age will cause physical and mental changes, there will be a decrease in the function and ability of a person. At the time of entering the elderly, automatically most elderly people will reduce their daily activities, which will affect their quality of life. The purpose of this community service activity is to provide education for the elderly on the types of activities and benefits. This activity was carried out in Angke Village, West Jakarta. This activity method is carried out by providing education, checking health status, and personal health consultations to the health team. This activity involved 22 elderly people. The results of the activity mean the age of the elderly is 68 years, and 86% of the participants are included in the age group < 75 years. As many as 68% of elderly participants had controlled chronic diseases, with hypertension being the most dominant. As many as 66% of the 22 elderlies were categorized as elderly with good activities.